Enhancing Organizational Effectiveness Through Employee Work Attitude: Dissection of Nigeria’s Hospitality Industry - Friday Ogbu Edeh; Mohammad Fakhrul Islam; Kevin Chukwuoyims Egwu; Collins Okechukwu Irem; Derrick Ssekajugo; Desmond Neji Oben; Benedict Dayo Olanipekun (AIBPM Publisher, 2024)
This study aims to examine the predictability of employee work attitude on the effectiveness of hospitality firms operating in Nigeria's work setting. Middle-line managers, supervisors, and low-level employees constitute the sample frame. To avoid bias in selection, simple random was used. Copies of the primary instrument were used to collect data. Frequency distribution was used to analyze respondents’ data while the research propositions were analyzed with linear regression with the aid of IBM SPSS statistical software version 25. The finding of the study showed that employee work attitude has a positive significant effect on organizational effectiveness. The study concluded that employee work attitude measured in terms of job satisfaction and job involvement enhances and improves the organizational effectiveness of hospitality firms in Nigeria through prompt service delivery and customer satisfaction. The implication of the study is that; supervisors, operations managers, and HR managers should pay positive attention to the attitude of their employees to discourage employee turnover that could lead to customer withdrawal.